Am I trolling?: A CA-informed approach to Gangjing in a Chinese online forum. (June 2022) - Xia, Jie; Wang, Ping
Highlights: A creative reference term Gangjing can perform communicative actions in an online forum. Gangjing is an interactional resource for accomplishing interpersonal functions. A CA-informed approach provides novel interpretations of online trolling discourse. Abstract: Because digital affordances of the Internet have provided spaces for linguistic creativity, a large number of popular terms derive from the Internet. Analyses of these forms serve as a lens through which essential aspects of social realities can be analyzed. This study focuses on the use of a trolling label Gangjing popularized in Chinese digital interaction. Collecting data from interactional threads in Baidu Post Bar, the CA-informed study investigates what communicative actions netizens perform in using the term and what responsive behaviors it triggers. Pragmatic notions such as identity construction and relational acts are adopted to interpret its use. Results show that Gangjing is used to show disagreements, delegitimize others as irrational participants, express negative emotional stances, and invite people for entertainment. Different responsive behaviors, including resisting, criticizing, mocking, attacking, and playing, are triggered. Overall, the creative trolling label can function as an interactional resource accomplishing interpersonal functions. By nuanced analyses of the dynamics of a popular reference term rooted in Chinese language and culture, the study adds to the current interactional approach to creative language use in online communication while providing new insight on interpretations of online trolling discourse.